Black Soldier Fly (Hermetia illucens) Oil Inclusion and its Effects on Growth Performances in Common Carp (Cyprinus carpio) - Vivi Endar Herawati; Heni Tri Jayanti; Tita Elfitasari; Sapto Purnomo Putro; Seto Windarto (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Use of maggot oil as an addition to feed can increase the level of feed consumption of carp. The addition of maggot oil ( illucens) had a significant effect (P<0.05) on TFC, FCR, FUE, SGR, and survival of common carp. The use of maggot oil can be an alternative to using feed that is more effective and economical.   Abstract The demand for common carp (Cyprinus carpio) either its seed or consumption measures has increased every year. Fish growth can be increased by adding nutrients in the form of animal oil sources. An alternative ingredient that can be used to support fish growth with good nutritional content and relatively inexpensive is maggot oil or black soldier fly (H. illucens) oil. The purpose of this study was to determine the effect of maggot oil (H. illucens) in artificial feed on the growth performance of common carp and to determine the best dose of maggot oil. This study used a complete randomized design (CRD) with four treatments and three replicates: A, B, C, and D with the addition of maggot oil doses of 0%, 10%, 15%, and 20%, respectively. The test fish used was a common carp fry measuring 3.59±0.06 cm, 0.79±0.05 g. Observation time was 30 days with a stocking density of 15 fish/aquarium. The results showed that the addition of maggot oil (H. illucens) had a significant effect (P<0.05) on TFC, FCR, FUE, SGR, and survival. Based on the results of the study, the best dose was obtained in the addition of 15% maggot oil with value of TFC 10.57±0.26 g, FCR 1.52±0.03, FUE 65.43±1.54%, SGR 1.57±0.04%/day, and SR 95.56±3.85%. For further research, it is possible to use magot oil to increase carp production.